Systematic bibliographic review on mathematical concepts and agribusiness in teaching learning for students in basic education (Research, Society and Development, 2021)
Agribusiness presents itself as one of the most important sectors for the development of the Brazilian economy, promoting employment and generating income through food production and growth in the agricultural sector. From this, it is essential to introduce theoretical and scientific concepts regarding the theme / sector, with the purpose of increasing productivity and profitability. Much conceptual framework applied in agricultural cultivation is acquired in elementary education, making the role of the primary school in the development of students and their ability to interpret and solve everyday situations, so that such content can be worked on in an interdisciplinary way. The present article aimed to carry out a Systematic Bibliographic Review (RBS) of scientific publications about mathematical modeling applied to agribusiness for high school students in the period from 2015 to 2019. Publications about the purpose present in this work are of paramount importance, since the analyzed results contributed significantly to identify the state of the art on the subject. It was observed that a large part of the contents related to the application of mathematics as an indispensable tool in agricultural production, becoming a daily and usual tool for the farmer.